2014
DOI: 10.1063/1.4864186
|View full text |Cite
|
Sign up to set email alerts
|

The surface structure of SrTiO3 at high temperatures under influence of oxygen

Abstract: Articles you may be interested in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…1a for bare SrTiO 3 . The starting surface shows clear diffraction spots and a 2 × 1 reconstruction, in line with earlier observations 25 . From the diffraction images, the peak intensity and full-width-halfmaximum (FWHM) of the specular spot were recorded and are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1a for bare SrTiO 3 . The starting surface shows clear diffraction spots and a 2 × 1 reconstruction, in line with earlier observations 25 . From the diffraction images, the peak intensity and full-width-halfmaximum (FWHM) of the specular spot were recorded and are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The LaAlO 3 /SrTiO 3 interfaces are grown and studied in an aberration corrected low-energy electron microscope (LEEM) at Leiden university, called ES-CHER [21][22][23][24] . The LEEM technique has been used before to study SrTiO 3 25 and LaAlO 3 26 separately. We now also developed a pulsed laser deposition (PLD) system inside the system to allow for analysis during growth, which was already used to study the growth of SrTiO 3 on SrTiO 3 18 .…”
Section: Experimental Setup and Sample Preparationmentioning
confidence: 99%
“…Specifically, the sign of the surface potential difference between regions initially consisting of nominally pure single terminations (SrO and TiO 2 ) is reversed. Whereas instability of STO surface under UHV conditions at elevated temperatures had been already reported [15], the present results emphasize chemical and electrostatic implications of surface reconstruction signaling a narrower temperature window of surface stability.…”
Section: Introductionsupporting
confidence: 75%
“…Specifically, the sign of the surface potential difference between regions initially consisting of nominally pure single terminations (SrO and TiO 2 ) is reversed. Whereas instability of STO surface under UHV conditions at elevated temperatures had been already reported [15], the present results emphasize chemical and electrostatic implications of surface reconstruction signaling a narrower temperature window of surface stability. EXPERIMENTAL (001)STO single-crystalline substrates from CrysTec GmbH were thermally treated at high temperature (≈1150 °C) in air for 2 h in a dedicated tubular furnace: in the following these samples are labeled "as-prepared".…”
Section: Introductionsupporting
confidence: 75%
“…At present, however, the surface of hybrid-grown STO films is poorly understood, making research on such complex heterostructures difficult to pursue. In spite of decades of studies, the stability of various STO surface terminations and reconstructions is still a matter of great debate [25][26][27][28]. In most SrTiO3 MBE film growth, in situ reflection high energy electron diffraction (RHEED) has been applied to monitor the growth in real time domain, though in-vacuo X-ray photoelectron spectroscopy (XPS) studies have never been reported.…”
Section: Introductionmentioning
confidence: 99%